2016
DOI: 10.1038/srep27854
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to BDE47 is associated with increased diabetes prevalence: Evidence from community-based case-control studies and an animal experiment

Abstract: Brominated flame retardants exposure has been associated with increasing trends of diabetes and metabolic disease. Thus, the purpose of this study was to provide evidence of polybrominated diphenyl ethers (PBDEs) exposure in relation to diabetes prevalence and to reveal the potential underlying mechanism in epidemiological and animal studies. All the participants received a questionnaire, health examination, and the detection of 7 PBDE congeners in serum in two independent community-based studies from 2011 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 34 publications
(47 reference statements)
1
50
0
Order By: Relevance
“…The inhibitory effects of DE-71 on both glucagon and insulin may indicate an altered capacity of -and -cell function in the pancreas, respectively. Interestingly, adult exposure to BDE-47 produced reduced gene expression for the rat GLP-1 receptor 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inhibitory effects of DE-71 on both glucagon and insulin may indicate an altered capacity of -and -cell function in the pancreas, respectively. Interestingly, adult exposure to BDE-47 produced reduced gene expression for the rat GLP-1 receptor 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that levels of insulin, glucagon and glucagon-like peptide 1 (GLP-1) are altered in T2D leading to pathological glucose dyshomeostasis 57 36 . Animal studies have failed to show changes in insulin levels with adult exposure to BDE-47 29 or postnatal exposure to BDE-47 31 or perinatal exposure to a mixture of BFRs, including PBDEs and HBCDD 52 . In 0.4 mg/kg F1 insulin reduction was less pronounced, and glucagon was decreased, which could explain the less marked glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult male mice exposed to DE‐71 exhibited increased glucose‐to‐insulin ratios, suggesting that exposure to the technical mixture can alter glucose homeostasis (Dunnick et al, ; Nash et al, ). Similarly, human studies have revealed that serum PBDE levels are higher in people with diabetes (Lim et al, ; Zhang et al, ). However, in these studies, exposure occurred during adulthood with concurrent testing, whereas, in the current study, exposure occurred during early life with later testing.…”
Section: Discussionmentioning
confidence: 73%